Dampak Sosial Media terhadap Pola Latihan dan Motivasi Atlet Amatir di Era Digital - Alif, M. Nur; Ali, M.; Jamaluddin, Juniarto (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2023)
This study aims to analyze the impact of social media on the training patterns and motivation of amateur athletes in the digital era. The digital era has transformed various aspects of human life, including sports. Social media has now become a platform used not only for social interaction but also as a source of information, inspiration, and motivation for amateur athletes in their training programs. This study used qualitative methods with a phenomenological approach, involving 30 amateur athletes from various sports in the Jakarta area and its surroundings. Data were collected through in-depth interviews, participant observation, and analysis of respondents' social media content. The results indicate that social media has a significant impact on amateur athletes' training patterns, both positively and negatively. Positive impacts include increased motivation through inspirational content, broader access to information on training techniques, and the formation of a supportive virtual community. However, negative impacts were also found, including psychological stress due to social comparison, the spread of inaccurate information, and the potential for addiction to social validation. This study concludes that social media use needs to be managed wisely to provide optimal benefits for amateur athletes' development without causing detrimental negative impacts.